Impact of capsaicin on aroma release: in vitro and in vivo analysis. (July 2020) - Yang, Ni; Galves, Cassia; Racioni Goncalves, Ana Carolina; Chen, Jianshe; Fisk, Ian
Graphical abstract: Highlights: The impact of capsaicin on aroma release was evaluated in a model system. Capsaicin did not modify equilibrium gas-liquid partitioning of aroma compounds. Capsaicin enhanced saliva secretion by 75% Capsaicin decreased in-nose aroma release of 3-methylbutanal, 1-octen-3-ol, and linalool. Capsaicin induced physiological changes (saliva flow) directly impacted aroma release. Abstract: Capsaicin is the main bioactive compound in chili pepper that leads to the perception of "spiciness". However, the effect of capsaicin on aroma release in the nose remains unexplained. This is the first study designed to measure capsaicin's impact on aroma release during consumption. In vitro studies, using static headspace analysis by atmospheric pressure chemical ionization-mass spectrometry (APCI-MS), showed no impact of capsaicin (5 ppm) on the gas-liquid partitioning equilibria of a range of aroma compounds. However, a significant reduction in aroma release was observed in vivo, during oral melting of a model ice cube system (p < 0.05) included 5 ppm capsaicin. The total release of aroma into the nasal cavity was decreased, such that only 49% of 3-methylbutanal, 60% of 1-octen-3-ol and 83% of linalool was released. This is the first evidence of capsaicin's reduction effect on aroma release during consumption. It was also found that 5 ppm capsaicin increased saliva secretion by 75%, which may have led to the dilution of aroma compounds in the mouth and directly impacted the aroma release into the nasal cavity. The most hydrophilic compound (3-methylbutanal) was affected by capsaicin to a greater extent than the hydrophobic compound (linalool), the solvent effect of the additional saliva may explain this.